Preclinical Evidence of Mulberry Leaf Polysaccharides on Diabetic Kidney Disease: a Systematic Review and Meta-Analysis - Wang, Yisu; Chen, Baifan; Zhang, Jinghong; Wang, Dan; Ruan, Yuan (Planta Medica, 2024)
Mulberry leaf polysaccharides (MLPs) have a variety of biological activities. Preliminary scattered evidence of preclinical studies have reported their potenzial effects on diabetic kidney disease (DKD). Here, we intended to assess the preclinical evidence of MLPs and explore their potenzial mechanisms on DKD, offering a scientific reference for the therapeutic use of MLPs. The study has been registered under the CRD42022309117 registration number at PROSPERO. Comprehensive search was conducted across eight databases from their establishment till January 2024, and eight studies with 270 animals were included in the meta-analysis. The primary outcome measurements in the MLP group, including serum creatinine (Scr) (P = 0.0005), blood urea nitrogen (BUN) (P = 0.02), 24-hour urinary protein (UP) (P = 0.001), and urinary microalbumin (UAlb) (P < 0.0001), were significantly reduced compared to the control group. Additionally, MLP treatment was significantly correlated with fasting blood glucose (FBG), total cholesterol (TC), protein expression of TGF-β1, CTGF mRNA, and the kidney index (all P values < 0.05) and delayed the progression of local pathological changes in the kidney. Subgroup analysis revealed significant species differences in the efficacy of MLPs. Also, it showed that the dosage of streptozotocin potenzially affected the Scr and UAlb results, while the duration of MLP treatment influenced UAlb results. MLPs may exert potenzial renal protection by delaying renal fibrosis, inhibiting inflammatory reactions, suppressing the growth hormone–insulin-like growth factor–insulin-like growth factor binding protein axis, and regulating the insulin receptor pathway. In summary, MLPs have multifaceted renal protective effects, suggesting their potenzial for treating DKD.
Keywords: mulberry leaf polysaccharides; DKD; meta-analysis; systematic review; renal protection; Moraceae; Morus